PENGOLAHAN EFFLUENT FERMENTOR BIOGAS SECARA AEROBIK MENGGUNAKAN REAKTOR ALIR TANGKI BERPENGADUK - Yohannes Tandean, Michael Vincent, Irvan, Bambang Trisakti (Jurnal Teknik Kimia USU, 2013)
Palm oil production in Indonesia is estimated around 28 million tonnes per annum. As this number increases, the waste generated from the process which generally called as palm oil mill effluent (POME)  increases as well. In Indonesia, POME treatment is being carried out conventionally by using facultative ponds system, which is high in operational cost, uses up a vast amount of land and generates greenhouse gas, Methane (CH4) as product which is usually burnt away. From previous researches done, POME has been treated anaerobically to produce biogas, but the effluent from these processes have not yet met the standard quality control required to be released to the environment. Which is why it still needs to be treated aerobically to fulfill the standar quality control so as to be released to the environment. From the research done by using continuous stirred tank reaktor and adding effective microorganism (EM4), the final VSS value reached was around 100 mg/L with 10 days HRT.